Elasticity of the individual knowledge represented by a system of concepts and its pilot investigation - Budrevičius, Algirdas (Information & Media, 2016)
The paper describes a model and an experimental exploration of elasticity of the individual knowledge represented by a system of concepts. The following conception of elasticity is used: the knowledge is elastic if it responds sensitively to the change of action exerted on this knowledge. The prerequisites and conditions of elasticity are defined. A method for experimental observation of knowledge elasticity is described and its pilot exploration is carried out. Elasticity is proposed to be explored by means of the observation of reactions of the individual. The reactions are described in terms of questions and answers. Each answer is meant to provide a list of concepts describing the content of the considered knowledge. The change of knowledge is provoked by a semantic difference between two questions; the change is observed as a difference between corresponding answers. The method is tested on a population of twelve students of an Information management study program in their final year (2012) of studies. The experiment supported the hypothesis that the knowledge of the most considered students is elastic.